Rediscovery and new records of adenocalymma (Bignonieae, Bignoniaceae) in Southeastern Brazil - Udulutsch, Renata Giassi [UNESP]; Dias, Pedro; Souza, Vinicius Castro (Magnolia Press, 2016)
Collecting expeditions carried out in São Paulo and Rio de Janeiro states have led to the rediscovery of Adenocalymma bullatum, known previously only by three collections made 70 years ago. New records of Adenocalymma bullatum from São Paulo and A. cinereum from São Paulo and Rio de Janeiro are reported. In addition, A. macrophyllum is rediscovered in Rio de Janeiro State after the type collections made 180 years ago by Friedrich Sellow. In this paper, we provide descriptions, comments on the affinities among closely related species, and conservation assessments, as well as illustrations.
Keywords: Atlantic forest; Endemism; IUCN categories; Seasonal semi-deciduous forest